Comparison of Photon Dose Distribution in Breast Cancer Using 3DCRT and Half Beam Techniques - Yusrani, Nurrohimawati; Robert Janssen Stevenly; Rahmawati Munir; Erlinda Ratnasari Putri (Jurnal Inotera, 2024)
Radiotherapy planning can be done with 3D Conformal Radiotherapy (3DCRT) and Half Beam. The success of radiotherapy planning is considered by comparing the isodose curve, Dose Volume Histogram (DVH), Organs At Risk (OAR), Homogeneity Index (HI), and Conformity Index (CI) obtained by the 3DCRT and Half Beam techniques. This study used data from 5 patients at the Radiotherapy Installation at A.W. Hospital. Sjahranie Samarinda with radiation planning of 5000 cGy (25×2 Gy) for breast cancer. The two radiation plans used gantry angles of 310˚ and 120˚. The calculated dose distribution value can be seen through the 90%, 95% PTV dose, and OAR absorbed dose. PTV doses of 90% and 95% in the 3DCRT technique covered the target well. The radiation dose values of the 3DCRT technique at PTV 90% were around 4860 cGy – 4930 cGy and PTV 95% were around 4750 cGy – 4840 cGy. Meanwhile, the Half Beam technique could not cover the target well. It was because the radiation dose values received by the Half Beam technique at 90% PTV were around 780 cGy – 4860 cGy and 95% PTV were around 2210 cGy – 5020 cGy. The OAR absorbed doses values for the 3DCRT and Half Beam techniques were still within the safe limits of tolerance according to QUANTEC. Meanwhile, the HI and CI values in the 3DCRT technique were closer to the rules of ICRU Report 83 of 2010 compared to the Half Beam technique. Therefore, from the values that have been obtained, the success rate of the radiotherapy planning process after measurements is shown in the 3DCRT technique. It has the value of more efficient dose calculations and can be used as a reference in optimizing dose distribution to patients.